The Selective Advantage of the lac Operon for Escherichia coli Is Conditional on Diet and Microbiota Composition - Pinto, Catarina (2021)
Funding Information: Funding: This work was funded by the Fundação para a Ciência e Tecnologia (PTDC/BIA-EVF/3247/2012 and PTDC/BIAEVL/30212/2017) and iBiMED (UID/BIM/04501/2019, project POCI-01-0145-FEDER-007628). CP was the recipient of a fellowship (138/BI/13) from Fundação para a Ciência e Tecnologia. RM-M was the recipient of a doctoral fellowship (DFA/BD/5130/2020) from Fundação para a Ciência e Tecnologia. AS was funded from National Funds through FCT - Fundação para a Ciência e a Tecnologia, I.P., under the Scientific Employment Stimulus - Institutional Call - reference CEECINST/00026/2018.